Combined effect of therapeutic strategies for bleeding injury on early survival, transfusion needs and correction of coagulopathy. Issue 3 (12th January 2017) - Balvers, K; van Dieren, S; Baksaas-Aasen, K; Gaarder, C; Brohi, K; Eaglestone, S; Stanworth, S; Johansson, P I; Ostrowski, S R; Stensballe, J; Maegele, M; Goslings, J C; et al.
Abstract: Background: The combined effects of balanced transfusion ratios and use of procoagulant and antifibrinolytic therapies on trauma-induced exsanguination are not known. The aim of this study was to investigate the combined effect of transfusion ratios, tranexamic acid and products containing fibrinogen on the outcome of injured patients with bleeding. Methods: A prospective multicentre observational study was performed in six level 1 trauma centres. Injured patients who received at least 4 units of red blood cells (RBCs) were analysed and divided into groups receiving a low (less than 1 : 1) or high (1 or more : 1) ratio of plasma or platelets to RBCs, and in receipt or not of tranexamic acid or fibrinogen products (fibrinogen concentrates or cryoprecipitate). Logistic regression models were used to assess the effect of transfusion strategies on the outcomes 'alive and free from massive transfusion' (at least 10 units of RBCs in 24 h) and early 'normalization of coagulopathy' (defined as an international normalized ratio of 1·2 or less). Results: A total of 385 injured patients with ongoing bleeding were included in the study. Strategies that were independently associated with an increased number of patients alive and without massive transfusion were a high platelet to RBC ratio (odds ratio (OR) 2·67, 95 per cent c.i. 1·24 to 5·77; P = 0·012), a high plasma to RBC ratio (OR 2·07, 1·03 to 4·13; P = 0·040) and treatment with tranexamic acid (OR 2·71, 1·29 to 5·71; P = 0·009). No strategies were associated with correction of coagulopathy. Conclusion: A high platelet or plasma to RBC ratio, and use of tranexamic acid were associated with a decreased need for massive transfusion and increased survival in injured patients with bleeding. Early normalization of coagulopathy was not seen for any transfusion ratio, or for use of tranexamic acid or fibrinogen products. Abstract : Combined effect on outcome